2014
DOI: 10.1161/circep.113.001477
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Remodeling of the Electrophysiological Response to Ischemia–Reperfusion in Human Heart Failure Is Associated With Remodeling of Metabolic Gene Expression

Abstract: Background Ventricular arrhythmias occur more frequently in heart failure during episodes of ischemia-reperfusion (I-R), although the mechanisms underlying this in humans are unclear. We assessed, in explanted human hearts, the remodeled electrophysiological response to acute I-R in heart failure, and its potential causes, including the remodeling of metabolic gene expression. Methods and Results We optically mapped coronary-perfused left ventricular wedge preparations from 6 human end-stage failing hearts (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…We previously studied the electrophysiological effects of acute myocardial ischemia in explanted human hearts using high-resolution optical mapping, 2,3 and reported progressive slowing of local conduction velocities with ischemia, consistent with the slowing of intra-atrial conduction observed in this study. Furthermore, we also mapped repolarization changes and confirmed the progressive shortening of action potential durations with ischemia in human.…”
Section: To the Editorsupporting
confidence: 85%
See 1 more Smart Citation
“…We previously studied the electrophysiological effects of acute myocardial ischemia in explanted human hearts using high-resolution optical mapping, 2,3 and reported progressive slowing of local conduction velocities with ischemia, consistent with the slowing of intra-atrial conduction observed in this study. Furthermore, we also mapped repolarization changes and confirmed the progressive shortening of action potential durations with ischemia in human.…”
Section: To the Editorsupporting
confidence: 85%
“…Both intraoperative recordings performed during acute ischemia, 4,5 and our work on explanted human hearts, 2,3 point towards the rapid onset of ischemia-induced electrophysiological changes in humans, with changes in conduction and repolarization firmly established approximately 10 minutes after onset of ischemia. Does the time course of electrophysiological changes in human atria mirror that of the ventricles?…”
Section: To the Editormentioning
confidence: 77%
“…In the presence of disease uncoupling may occur, as in heart failure, and M cell behavior might become apparent. However, Ng et al did not find M cell behavior in wedge preparations from human end-stage failing hearts (Ng et al, 2014).…”
Section: Transmural Gradients In Repolarization: Where Are the M-cells?mentioning
confidence: 95%
“…Other studies using optical and electrical mapping have demonstrated that the transmural repolarization gradient is small and cannot entirely account for the duration of the T-wave (Anyukhovsky et al, 1999;Boukens et al, 2015;Janse et al, 2011;Meijborg et al, 2014;Rodriguez-Sinovas et al, 1997). Furthermore, recent studies in human left ventricular wedge preparations did not show a subpopulation of M-cells Glukhov et al, 2012;Glukhov et al, 2010;Ng et al, 2014). Lou et al did observe a small island of myocytes in the midmyocardium with longer action potential than the adjacent subendocardial or subepicardial myocytes in 3 out of 5 preparations (Lou et al, 2011).…”
Section: Transmural Gradients In Repolarization: Where Are the M-cells?mentioning
confidence: 97%
“…While KCNJ11 transcript levels in patients with heart failure have been reported, the patient population in the study was not specifically ICM, but rather a group with mixed etiologies of heart failure. 33 The current study specifically compared known ICM patient samples to control patient samples thereby, definitively establishing that KCNJ11 transcript level is decreased in ICM. Prior work has suggested K ATP channel expression and function is decreased with age in animal models 34, 35 , however, this was predominantly due to a decrease in SUR2A gene expression.…”
Section: Discussionmentioning
confidence: 79%